2014
DOI: 10.1121/1.4885482
|View full text |Cite
|
Sign up to set email alerts
|

Temporal characteristics of speech: The effect of age and speech style

Abstract: Aging affects temporal characteristics of speech. It is still a question how these changes occur in different speech styles which require various cognitive skills. In this paper speech rate, articulation rate, and pauses of 20 young and 20 old speakers are analyzed in four speech styles: spontaneous narrative, narrative recalls, a three-participant conversation, and reading aloud. Results show that age has a significant effect only on speech rate, articulation rate, and frequency of pauses. Speech style has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 10 publications
3
32
2
3
Order By: Relevance
“…The obtained results are supported by previous studies 6,8,14,22,23 that showed speech and articulation rates decrease and duration and frequency of pauses increase through aging.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The obtained results are supported by previous studies 6,8,14,22,23 that showed speech and articulation rates decrease and duration and frequency of pauses increase through aging.…”
Section: Discussionsupporting
confidence: 81%
“…The first 5 minutes of participants' speech were analyzed. 14 After recording samples, varieties of disfluencies were identified in two groups, including stuttering-like disfluencies (SLD), such as syllable repetition, sound repetition, prolongation, blocks, pauses, and intrusion of sounds or segments, and other disfluencies (OD) including hesitation, interjection, revision, non-finished words, word repetition, and segment repetition or phrase repetition. 6 Then, frequency of various disfluencies (number of disfluencies in 100 words) was calculated.…”
Section: Procedures and Measuresmentioning
confidence: 99%
See 3 more Smart Citations